Ancient Syria : a three thousand year history - Bryce, Trevor, 1940- (Oxford University Press, 2014)
Syria has long been one of the most trouble-prone and politically volatile regions of the Near and Middle Eastern world. This book looks back beyond the troubles of the present to tell the 3000-year story of what came before: the peoples, cities, and kingdoms that arose, flourished, declined, and disappeared in the lands that now constitute Syria, from the time of the region's earliest written records in the third millennium BC, right through the reign of the Roman emperor Diocletian in the early 4th century AD.